2019
DOI: 10.1029/2019jd030662
|View full text |Cite
|
Sign up to set email alerts
|

The Summertime Precipitation Bias in E3SM Atmosphere Model Version 1 over the Central United States

Abstract: This study analyzes the summertime precipitation bias over the Central United States and its relationship to the simulated large‐scale environment and the convection scheme in the Energy Exascale Earth System Model Atmosphere Model version 1. This relationship is mainly examined in a set of short‐term hindcasts initialized with realistic large‐scale conditions for the summer of 2011. Besides the uniform 1° model resolution, we adopt Regionally Refined Meshes to increase the model resolution to 0.25° over the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 88 publications
7
12
0
Order By: Relevance
“…The NEXRAD observations used in this study reveal that EAMv1 fails to simulate the occurrence of large ice-phase particles at high levels in deep convective clouds. In addition, the conclusion that "simulated deep convection is not deep enough" also echoes the dry bias seen in GCMs as manifested in underestimations of total precipitation and individually large rain rates over the CONUS (e.g., Zheng et al, 2019). We have now shown that this model deficiency cannot be significantly improved by tuning a single value of the physical parameters in the ZM cumulus and MG2 cloud microphysics schemes.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The NEXRAD observations used in this study reveal that EAMv1 fails to simulate the occurrence of large ice-phase particles at high levels in deep convective clouds. In addition, the conclusion that "simulated deep convection is not deep enough" also echoes the dry bias seen in GCMs as manifested in underestimations of total precipitation and individually large rain rates over the CONUS (e.g., Zheng et al, 2019). We have now shown that this model deficiency cannot be significantly improved by tuning a single value of the physical parameters in the ZM cumulus and MG2 cloud microphysics schemes.…”
Section: Conclusion and Discussionmentioning
confidence: 62%
“…As evaluated in Zheng et al (2019), E3SM v1 failed to simulate the diurnal variation of precipitation over the central US, where the observed nocturnal peak is greatly underestimated. Xie et al (2019) improved the diurnal cycle of convection in E3SM v1 recently by modifying the convective trigger function in the ZM scheme.…”
Section: Comparison Of Vertical Distribution Of Radar Reflectivitymentioning
confidence: 99%
“…EAMv1 was found to have difficulties in capturing the observed diurnal cycle of precipitation and propagation of mesoscale convective systems in both midlatitude and tropics, particularly the nocturnal peaks over these regions (Rasch et al, 2019; Tang, Klein, et al, 2019; Zheng et al, 2019). With the revised convective trigger for ZM, Xie et al (2019) showed that the phase of diurnal cycle of precipitation simulated by EAMv1 was significantly improved.…”
Section: Scm Testmentioning
confidence: 99%
“…As a result, model convection is triggered too easily during the day particularly over land in summer. This also partially causes the failure of capturing nocturnal convection in many models (Lee et al, 2007(Lee et al, , 2008Surcel et al, 2010;Zheng et al, 2019) since nocturnal convection is often elevated and decoupled from the surface (Geerts et al, 2017;Marsham et al, 2011;Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over ocean, the amplitude of the diurnal cycle is typically too weak, and the peak time does not match the observations (Dai, 2006). These problems are known to be closely related to the convection trigger function used in the convective parameterizations (e.g., Dai & Trenberth, 2004; Lee et al., 2008; Wang et al., 2020; Xie & Zhang, 2000; Xie et al., 2019; Xie, Zhang, Boyle, et al., 2004; X. Zheng et al., 2019).…”
Section: Introductionmentioning
confidence: 99%